Stably Integrated for Assessment of Invasion Kinetics - Kelly N. Flentie; Min Qi; Seth T. Gammon; Yasmin Razia; Felix Lui; Luciano Marpegan; Aashish Manglik; David Piwnica-Worms; Jeffrey S. McKinney (Molecular Imaging)
Salmonella Typhimurium is a common cause of gastroenteritis in humans and also localizes to neoplastic tumors in animals. Invasion of specific eukaryotic cells is a key mechanism of Salmonella interactions with host tissues. Early stages of gastrointestinal cell invasion are mediated by a Salmonella type III secretion system, powered by the adenosine triphosphatase invC. The aim of this work was to characterize the invC dependence of invasion kinetics into disparate eukaryotic cells traditionally used as models of gut epithelium or neoplasms. Thus, a nondestructive real-time assay was developed to report eukaryotic cell invasion kinetics using lux+ Salmonella that contain chromosomally integrated luxCDABE genes. Bioluminescence-based invasion assays using lux+ Salmonella exhibited inoculum dose-response correlation, distinguished invasion-competent from invasion-incompetent Salmonella , and discriminated relative Salmonella invasiveness in accordance with environmental conditions that induce invasion gene expression. In standard gentamicin protection assays, bioluminescence from lux+ Salmonella correlated with recovery of colony-forming units of internalized bacteria and could be visualized by bioluminescence microscopy. Furthermore, this assay distinguished invasion-competent from invasion-incompetent bacteria independent of gentamicin treatment in real time. Bioluminescence reported Salmonella invasion of disparate eukaryotic cell lines, including neoplastic melanoma, colon adenocarcinoma, and glioma cell lines used in animal models of malignancy. In each case, Salmonella invasion of eukaryotic cells was invC dependent.